Wideband Rectangular Foldable and Non-foldable Antenna for Internet of Things Applications - Steve W. Y. Mung; Cheuk Yin Cheung; Ka Ming Wu; Joseph S. M. Yuen (International Journal of Antennas and Propagation)
This article presents a simple wideband rectangular antenna in foldable and non-foldable (printed circuit board (PCB)) structures for Internet of Things (IoT) applications. Both are simple structures with two similar rectangular metal planes which cover multiple frequency bands such as GPS, WCDMA/LTE, and 2.4 GHz industrial, scientific, and medical (ISM) bands. This wideband antenna is suitable to integrate into the short- and long-range wireless applications such as the short-range 2.4 GHz ISM band and standard cellular bands. This lowers the overall size of the product as well as the cost in the applications. In this article, the configuration and operation principle are presented as well as its trade-offs on the design parameters. Simulated and experimental results of foldable and non-foldable (PCB) structures show that the antenna is suited for IoT applications.